Simplified Fabrication of Surgical Template for Orthodontic-Implant Treatment - Cortino Sukotjo, DDS, PhD1 and Virginia Bocage, DDS2 (Journal of Prosthodontics, 2006)
COMPREHENSIVE, MULTIDISCIPLINARY treatment planning is key to a successful oral rehabilitation